TEST EQUIPMENT SPECIFICATIONS TRANSISTOR - Didiek Andiana Ramadan; Drs. Linga Hermanto, MMSI Drs. Linga Hermanto, MMSI (Jurnal Sistem Komputer, 2005)
In this paper, we design a test apparatus Transistor Specification. Specification is atype of transistor is a transistor and common emitter current reinforcement value ( Î²DC ). The system will provide information in the form of an LED display emits greenlight when the tested types of NPN transistor and the second LED emits blue lightwhen the tested types of PNP transistors.To test the value of Î², whose value is proportional to the display used by the collectorcurrent Ic.